RETRACTED: CCDC88A Post-Transcriptionally Regulates VEGF via miR-101 and Subsequently Regulates Hepatocellular Carcinoma - Hu, Qiongying; Li, Yuchen; Chen, Hongqing; Liao, Hongyan; He, Yong; Zheng, Qin (Frontiers in Immunology, 2022)
Background: miR-101 is one of the most abundantly expressed microRNA (miRNA) and exert critical role in hepatocellular carcinoma (HCC) by targeting to 3’ -untranslated region (UTR) of Girders of actin filaments (CCDC88A) and Vascular endothelial growth factor (VEGF) mRNA, but the underlying molecular mechanism remains to be elucidated. This study aimed to investigate the potential role of CCDC88A on malignancies and stemness, by regulating VEGF via miR-101 in HCC. Methods: Gene Expression Profiling Interactive Analysis (GEPIA) was employed to analyze relevance of CCDC88A expression with prognosis in HCC. Tissue slides were performed to confirm the protein level of CCDC88A in HCC. Correlation between CCDC88A and VEGF was transcriptionally and post-transcriptionally detected, followed by evaluation of malignancies. Results: By employing Immunohistochemistry, we found CCDC88A protein was upregulated in HCC tissues, which is closely correlated to poor prognosis and survival rate. Employment of GEPIA revealed the positive correlation between CCDC88A and VEGF in HCC, but not in liver tissue. Silencing of CCDC88A in Huh-7 and SK-HEP-1 cells, significantly decreased the proliferation, cell cycle phases, migration, invasion, colony formation and tumor formation. Introduction of miR-101 mimics specifically targeting to CCDC88A and VEGF specifically decreased protein levels of both CCDC88A and VEGFA. Notably, inhibition of miR-101 reversed the correlation between CCDC88A and VEGFA protein levels, indicated that CCDC88A and VEGF may exert as a miR-101 sponge. Addition of SKLB1002, a VEGFR2 inhibitor inhibited malignant behaviors, which was further inhibited by introduction of miR-101 mimics, indicated that CCDC88A regulates malignant behaviors partially via regulating VEGF. Moreover, CCDC88A also promotes stemness of cancer stem-like cells derived from HCC cells depending on VEGF modification. Conclusion: Taken together, our findings suggested that miR-101/CCDC88A/VEGF axis could be a potential therapeutic target of HCC treatment.